Dog activity monitoring sensor - Chieng, Fang Ling (2017)
The paper reviews the lack of data by researchers to study the movements of wildlife. There were numerous attacks reported in Singapore, which cause residents to be worried for the safety of the public and extinction of small animals. A detailed analysis was made to understand the behaviours of the wild dogs to best integrate the useful and appropriate features into the project to track their movements. In this project, it is aim to build a portable dog activity sensor that is ergonomic to be worn on the dogs' collar which has the capability to capture real time surrounding images, GPS location, activity data, environment data with auxiliary data acquisition capability in order to enable researchers to perform meaningful analysis.